Integrated Health and Social Care in England: Ten Years On - Robin Miller (Ubiquity Press, 2021)
Introduction: As part of major policy reforms begun in 2010, England introduced a wave of initiatives to encourage more integrated care between health and social care. These built on previous attempts which sought to achieve similar objectives through a focus on better partnership working. This article provides an overview and critical commentary on integrated care policy in England from 2010–2020 based on reviews by regulators, parliamentary committees and the national audit office. Overview of Policy: Integrated care became a priority through the work of the Future Forum, a group of leading stakeholders established due to concerns about greater competition in public health care. This led to a public statement of shared commitment to integrated care by national health and social care bodies. Early mechanisms included a pooled fund to achieve nationally set objectives, the creation of local authority led partnership boards, and high profile innovation programmes. Later in the 2010’s, new health led partnerships became more dominant vehicles to achieve integrated care at regional level. Impact of Policy: Despite progress within a few local areas, and reduction in delayed discharges from hospital the overall picture from national reviews was that expected improvements were not achieved. Emergency admissions to hospital continued to grow, patients within primary care reported being less involved in their care, and health inequalities worsened. The initial response to COVID-19 was health-centric contributing to outbreaks in care homes and inadequate supplies of protective personal equipment. The ability of leaders to look beyond their organisations’ interests was reported as vital for local progress. National government performance frameworks discouraged system based working and chronic underfunding of social care led to major capacity and workforce challenges. Conclusion: The experience of England suggests that greatest progress is made when integrated care focusses on tangible issues and when there is a clear understanding of how success will be measured. Even with considerable investment and intent progress should be expected to be slow and difficult. Layering of numerous policy initiatives provides confusion and can distract from the important work of relationship building. And ultimately, integrated care cannot by itself address major inadequacies in the underlying resources and structural inequalities.